"[A]ll just surface and veneer": the challenge of seeing and reading in Ishtiyaq Shukri's I See You. Issue 4 (2nd October 2017) - Dass, Minesh
Abstract: This article considers challenges posed to reading practices and hermeneutics by Ishtiyaq Shukri's I See You . The content of the novel is at times didactic, and surface reading might seem an appropriate means of analysis, yet the form is experimental: it includes radio reports, characters' reflections and journalistic work. The connection between these "documents" is not readily apparent, thus one is obliged to study the gaps between them to make sense of the text. Symptomatic reading might seem apposite, but the protagonist's photographic work reveals the limits of this form of reading, too. I argue that Shukri's text demands a process that interweaves symptomatic and surface reading in complex ways that require the reader to assess the ideological position from which s/he reads. The novel therefore draws attention to the ways in which reading, like seeing, is a political act.